2004
DOI: 10.1007/s00432-004-0656-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral capecitabine plus subcutaneous interferon alpha in advanced squamous cell carcinoma of the skin

Abstract: The treatment protocol with a combination of capecitabine and interferon alpha seems to be effective and well tolerated in patients with advanced SCC. Controlled trials are necessary to prove the benefit we observed in this case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…The final outcome was complete remission in two patients and progressive disease in one patient; however, the authors state that controlled trials are necessary to prove the benefit observed in this series. 37 Capecitabine is a prodrug of 5-deoxy-5-fluorouridine. It is metabolized in the liver to 5-FU by thymidine phosphorylase, which is overexpressed in some human carcinomas.…”
Section: Capecitabinementioning
confidence: 99%
“…The final outcome was complete remission in two patients and progressive disease in one patient; however, the authors state that controlled trials are necessary to prove the benefit observed in this series. 37 Capecitabine is a prodrug of 5-deoxy-5-fluorouridine. It is metabolized in the liver to 5-FU by thymidine phosphorylase, which is overexpressed in some human carcinomas.…”
Section: Capecitabinementioning
confidence: 99%
“…Wollina et al [19] used oral capecitabine and s.c. IFN-␣ in four patients with advanced cutaneous SCC. Capecitabine is an orally bioavailable fluoropyrimidine chemotherapy agent that is converted to 5-FU in tumor cells.…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%
“…Wollina et al [ 17 ] performed a prospective case series of four patients with advanced CSCC treated with oral capecitabine plus subcutaneous interferon alpha, of which two patients had complete response and two a partial response. Of note, the patients had only mild side effects.…”
Section: Induction and Defi Nitive Chemotherapy For Advanced Csccmentioning
confidence: 98%